1991
DOI: 10.1021/jf00002a023
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the content of lipid autoxidation and sulfur-containing compounds in cooked beef during storage

Abstract: Changes in the content of carbonyl-and sulfur-containing compounds were determined for ground beef patties stored at 4 °C for 0-4 days. Volatile compounds were isolated by using distillation-extraction techniques and analyzed by using gas chromatography and mass spectrometry. During storage, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(104 citation statements)
references
References 36 publications
9
95
0
Order By: Relevance
“…During oxidative degradation of unsaturated fatty acids, present in meat systems, undesirable flavour and odour occur, due to the formation of aldehydes, ketones and alcohols (Drumm and Spanier, 1991). In the present work, the trend observed in WOF values was consistent with the values of the antioxidant activity of the additives and packaging method (Tables 1, 4 and 5).…”
Section: Microorganismssupporting
confidence: 88%
“…During oxidative degradation of unsaturated fatty acids, present in meat systems, undesirable flavour and odour occur, due to the formation of aldehydes, ketones and alcohols (Drumm and Spanier, 1991). In the present work, the trend observed in WOF values was consistent with the values of the antioxidant activity of the additives and packaging method (Tables 1, 4 and 5).…”
Section: Microorganismssupporting
confidence: 88%
“…Similar results were reported for fresh beef, pork and fish (Morrissey and Apte, 1988), for chevon (Lamikanra and Dupuy, 1990), for salted and dried beef (Torres et al, 1989) and for cooked beef (Drumm and Spanier, 1991). The latter authors have also shown that hexanal concentration increases much faster than any other aldehyde during the storage of cooked beef (Figure 14.9).…”
Section: Hexanal and Other Carbonyl Compoundssupporting
confidence: 82%
“…Figure 14.9 Relationship between hexanal (main plot), and hexanaI and other volatiles (insert plot), and storage period of beef patties (Drumm and Spanier, 1991).…”
Section: Hexanal and Other Carbonyl Compoundsmentioning
confidence: 99%
“…16,17) Being a potential autoxidation product of linoleic acid, 18) 2-pentylfuran showed the highest ratio of concentration in warmed-over flavor beef to freshcooked beef, 19) and a higher relative concentration of 2-pentylfuran was detected in this study. Besides, dodecane and 2,4-decadienal were identified in cooked longissimus muscle from different breeds by Lu et al 6) For 3-methyl-1-butanol, it could give an olfactory sensation of fresh-cured pork flavor in short ripening process.…”
Section: Breedsupporting
confidence: 49%